2023
DOI: 10.3390/ma16051761
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Final Irrigation Protocol on the Push-Out Bond Strength of Two Types of Endodontic Sealers

Abstract: Aim: The aim of this study was to assess the impact of the final irrigation protocol on the push-out bond strength of calcium silicate-based sealers when compared to an epoxy resin-based sealer. Materials and Methods: Eighty-four single-rooted mandibular human premolars were shaped using the R25® instrument (Reciproc, VDW, Munich, Germany) and then divided into three subgroups of 28 roots each depending on the final irrigation protocol: EDTA (ethylene diamine tetra acetic acid) and NaOCl activation, Dual Rinse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Bioceramic cements containing nanoparticles also showed significantly lower porosity ( Yalniz et al, 2024 ). Using a chelating irrigant to remove the intracanal medicament may have improved Bio-C Repair’s adhesion to dentin by opening the dentinal tubules and facilitating the penetration of its smaller particles into them ( Kadić et al, 2018 ; Sfeir et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bioceramic cements containing nanoparticles also showed significantly lower porosity ( Yalniz et al, 2024 ). Using a chelating irrigant to remove the intracanal medicament may have improved Bio-C Repair’s adhesion to dentin by opening the dentinal tubules and facilitating the penetration of its smaller particles into them ( Kadić et al, 2018 ; Sfeir et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison of nine articles that categorized samples based on the final irrigant used in each intervention group, it was observed that 17% EDTA as a final irrigant increased the adhesion strength of the CSCs [16,29,43,47]. The alkaline pH of EDTA induces an abundance of hydroxyl ions, leading to smear layer dissociation, reduced chelation with calcium ions, and a slow dissolution of inorganic and organic components, resulting in higher surface roughness and favorable wettability, all contributing to elevated bond strength values.…”
Section: Final Irrigantmentioning
confidence: 99%
“…The following supporting information can be downloaded at https: //www.mdpi.com/article/10.3390/app14010104/s1, Table S1: POBS results from the included studies. References [3,[35][36][37]39,40,[42][43][44][45][46][47][48][49][50]52] are cited in the Supplementary Materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…It has been demonstrated that using ethylenediaminetetraacetic acid (EDTA) and sodium hypochlorite together makes the surface hydrophobic and improves the adherence of AH Plus (Dentsply) sealers [ 10 ]. According to a study, the push-out method was more accurate and dependable than the micro-tensile method for determining bond strength to dentin [ 11 ].…”
Section: Introductionmentioning
confidence: 99%